Effects of prior knowledge on collaborative and individual learning. (October 2019) - Zambrano R., Jimmy; Kirschner, Femke; Sweller, John; Kirschner, Paul A.
Abstract: Collaborative learning is an extensively used instructional technique by which individuals interact in small groups to learn to solve academic problems. This study aimed to determine the impact of task-specific prior knowledge on individual learners and collaborative groups that were instructed to collaborate. A 2 (individual vs. collaborative group) × 2 (novice vs. knowledgeable learners) factorial experiment with 228 students was carried out to examine the effects of these treatments on performance and mental effort in learning and its outcomes. As expected, knowledgeable individuals and knowledgeable collaborative groups outperformed novice individuals and novice collaborative groups in learning outcomes. Less knowledgeable, collaborating learners outperformed less knowledgeable, individual learners in learning outcomes. While more knowledgeable collaborating and individual learners performed equally well in the learning phase and the delayed test, on the retention test, collaborative groups demonstrated better performance. In general, collaboration benefited learning compared to individual learning in complex tasks, but performance depended on the learner task-specific prior knowledge. Highlights: Prior knowledge benefits collaborative and individual learning in complex tasks. The effects of prior knowledge are more observable in learning outcomes. Collaborative learning with advanced learners is redundant.